Exofucosylation of Adipose Mesenchymal Stromal Cells Alters Their Secretome Profile - García-Bernal, David; García-Arranz, Mariano; García-Guillén, Ana I.; García-Hernández, Ana M.; Blanquer, Miguel; García-Olmo, Damián; Sackstein, Robert; Moraleda, Jose M.; Zapata, Agustín G. (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stromal cells (MSCs) constitute the cell type more frequently used in many regenerative medicine approaches due to their exclusive immunomodulatory properties, and they have been reported to mediate profound immunomodulatory effects in vivo. Nevertheless, MSCs do not express essential adhesion molecules actively involved in cell migration, a phenotypic feature that hampers their ability to home inflamed tissues following intravenous administration. In this study, we investigated whether modification by fucosylation of murine AdMSCs (mAdMSCs) creates HCELL, the E-selectin-binding CD44 glycoform. This cell surface glycan modification of CD44 has previously shown in preclinical studies to favor trafficking of mAdMSCs to inflamed or injured peripheral tissues. We analyzed the impact that exofucosylation could have in other innate phenotypic and functional properties of MSCs. Compared to unmodified counterparts, fucosylated mAdMSCs demonstrated higher in vitro migration, an altered secretome pattern, including increased expression and secretion of anti-inflammatory molecules, and a higher capacity to inhibit mitogen-stimulated splenocyte proliferation under standard culture conditions. Together, these findings indicate that exofucosylation could represent a suitable cell engineering strategy, not only to facilitate the in vivo MSC colonization of damaged tissues after systemic administration, but also to convert MSCs in a more potent immunomodulatory/anti-inflammatory cell therapy-based product for the treatment of a variety of autoimmune, inflammatory and degenerative diseases.